Associations Between MMPI-2-RF Internalizing RC Scales and Positive Characteristics. Issue 1 (2nd January 2021) - Hall, Jordan T.; Lee, Tayla T.C.; Ajayi, William; Friedhoff, Lesley Ann; Graham, John R.
Abstract: Past studies indicate that the low scores on the MMPI and MMPI-2 Clinical and Content Scales can reflect positive characteristics. It is currently unclear, however, whether scales on the MMPI-2-Restructured Form (MMPI-2-RF) have that ability. Accordingly, we examined whether low scores on Restructured Clinical (RC) Scales assessing internalizing difficulties (i.e., RCd, RC2, and RC7) can reflect self-esteem, life satisfaction, positive and negative affect, and optimism. When considering the full range of scores, each of the internalizing RC Scales demonstrated the expected pattern of associations with these characteristics. Across difference and percentage bend analyses, however, only RC2 had significant associations—namely, with positive affect, self-esteem, and life satisfaction. This study corroborates that high scores on the internalizing RC scales have interpretations consistent with past literature, but also uniquely suggests that below average RC2 scores may reflect increased positive affect, self-esteem, optimism, and satisfaction with life.